Strategic global sourcing best practices - Sollish, Fred.; Semanik, John. (Hoboken, N.J. : Wiley, 2011)
"The latest best practice guidance on all aspects of global strategic sourcing-including environmental and international issues Best Practices in Global Strategic Sourcing covers the latest trends and leading edge processes in global strategic sourcing, including supply management, t, sustainability, financial decisions, risk management, and international strategies. Offers the latest trends and guidance for sourcing and supply managers Features coverage of understanding sourcing, procurement and supply management, procurement and best business practices, best practices in sourcing management and global sourcing management, financial strategies for sourcing, responsible procurement,diversity procurement, managing risk, supplier selection, project management for procurement and supply managers, managing supplier relationships, international sourcing, managing supplier relationships supply management operations, With the rise of global supply chains, environmental/sustainability concerns, and constantly evolving technology, the time is right for understanding Best Practices in Global Strategic Sourcing."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Industrial procurement; Purchasing; Strategic planning; Business logistics